2020
DOI: 10.3390/nu12072037
|View full text |Cite
|
Sign up to set email alerts
|

Omega-3 Phospholipids from Krill Oil Enhance Intestinal Fatty Acid Oxidation More Effectively than Omega-3 Triacylglycerols in High-Fat Diet-Fed Obese Mice

Abstract: Antisteatotic effects of omega-3 fatty acids (Omega-3) in obese rodents seem to vary depending on the lipid form of their administration. Whether these effects could reflect changes in intestinal metabolism is unknown. Here, we compare Omega-3-containing phospholipids (krill oil; ω3PL-H) and triacylglycerols (ω3TG) in terms of their effects on morphology, gene expression and fatty acid (FA) oxidation in the small intestine. Male C57BL/6N mice were fed for 8 weeks with a high-fat diet (HFD) alone or sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 78 publications
(102 reference statements)
1
20
0
Order By: Relevance
“…Experiments were performed similarly as before [13,19,20,39]. Thus, male C57BL/6N mice (Charles River Laboratories, Sulzfeld, Germany) were maintained at 22 • C in a 12 h light-dark cycle (light from 6.00 a.m.) with free access to water and standard chow diet (STD; 3.4% wt/wt as lipids; rat/mouse-maintenance extrudate; Ssniff Spezialdieten GmbH, Soest, Germany).…”
Section: Animals and Dietary Interventionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Experiments were performed similarly as before [13,19,20,39]. Thus, male C57BL/6N mice (Charles River Laboratories, Sulzfeld, Germany) were maintained at 22 • C in a 12 h light-dark cycle (light from 6.00 a.m.) with free access to water and standard chow diet (STD; 3.4% wt/wt as lipids; rat/mouse-maintenance extrudate; Ssniff Spezialdieten GmbH, Soest, Germany).…”
Section: Animals and Dietary Interventionsmentioning
confidence: 99%
“…Blood glucose levels were measured by OneTouch Ultra glucometers (LifeScan, Milpitas, CA, USA), and plasma insulin levels were determined by the Sensitive Rat Insulin RIA Kit (Millipore, Billerica, MA, USA). Liver TAG content was estimated in ethanolic KOH tissue solubilisates as before [13].…”
Section: Biochemical Analysis Of Plasma and Tissue Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in line with our current and previous [ 29 ] results documenting the improved bioavailability of EPA at the level of liver PLs. Furthermore, a recent study on mice fed a high-fat diet based on corn oil suggests that intestinal FA oxidation, which was more effectively stimulated by krill oil compared to omega-3 PUFAs supplemented as TAGs, could also be involved in the antisteatotic effects of this marine oil [ 59 ]. It is worth mentioning that other bioactive constituents are present in krill oil, which may possess antisteatotic and insulin-sensitizing properties.…”
Section: Discussionmentioning
confidence: 99%
“…Further evidence suggested that omega-3 phospholipids of krill oil enhanced intestinal fatty acid oxidation and could contribute to the anti-steatotic effects in obese mice, meaning there could exist an axis microbiota-intestine-liver [116]. Indeed, omega-3 alleviated hepatic steatosis in various rodent models of obesity even in exacerbated hepatic steatosis conditions, in which an HFD was combined with thermoneutral animal housing (i.e., ambient temperature approximately 30 • C) [117].…”
Section: Krill and Metabolic Disordersmentioning
confidence: 99%